2001
DOI: 10.1080/jmf.10.2.131.135
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid for the treatment of intrahepatic cholestasis of pregnancy

Abstract: O bje ctive: To report our experience in managing intrahepatic cholestasis of pregnancy with ursodeoxycholic acid. Meth ods: All cases of intrahepatic cholestasis of pregnancy that were diagnosed at Bridgeport Hospital from January 1997 to August 1999 were identified. Information was abstracted on demographics, medical and obstetric history, symptoms, laboratory data, therapy and pregnancy outcome. Statistical analysis was primarily descriptive; continuous variables were analyzed with t tests. Re sults: A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 7 publications
1
17
1
1
Order By: Relevance
“…10 The prevalence of ICP in the United States has been reported from two studies to be between 0.001 and 0.32%. 10,11 The reported low prevalence in the United States is contrary to our clinical observation of treating ICP at the University of Southern California in Los Angeles. To our knowledge, there is no prevalence data on ICP in the Latina population based in the United States.…”
Section: Introductioncontrasting
confidence: 60%
See 1 more Smart Citation
“…10 The prevalence of ICP in the United States has been reported from two studies to be between 0.001 and 0.32%. 10,11 The reported low prevalence in the United States is contrary to our clinical observation of treating ICP at the University of Southern California in Los Angeles. To our knowledge, there is no prevalence data on ICP in the Latina population based in the United States.…”
Section: Introductioncontrasting
confidence: 60%
“…The pruritus scale resulted with maximum sensitivity and negative predictive values with a pruritus score threshold of >4 for detecting ICP as defined as serum bile acid X20 mmol/l, which agrees with our original definition of ICP in this study. 11 Before this study, the prevalence of ICP in the United States had been reported to be on the order of 7/1000 and less than 1/1000 patients. 13,14 Our comparatively higher prevalence (5.6%) could possibly be attributed to the primarily Latina patient population whom we serve.…”
Section: Resultsmentioning
confidence: 92%
“…Since then, other groups have reported similar effects in open series and case reports [3,[29][30][31][32][33], and four randomized controlled trials have been published [34,35,36•,37]. However, methodologic differences limit the validity of pooling results from these studies [38].…”
Section: Ursodeoxycholic Acidmentioning
confidence: 72%
“…For unknown reasons, the prevalence has more recently appeared to decrease (to between 4.0% and 6.5%) [15,16]. In the United States, the prevalence has been estimated from 0.3% to 5.6% according to ethnic origin [17,18]. The prevalence is Europe is about 0.5-1.5% [13].…”
Section: Intrahepatic Cholestasis Of Pregnancymentioning
confidence: 97%